Mediation Role of Financial Attitude on The Influence of Financial Knowledge on Financial Behavior - Jufrizen, Jufrizen; Ariza, Cintya (Journal Of Management Analytical and Solution (JoMAS), 2022)
The aim of this study was to determine the impact of financial knowledge on financial behavior on financial attitudes, which were the mediating variable for students of the Faculty of Business and Economics, Mohammed North Sumatra University. The study is of the associative type of study, which collects technical data through questionnaires (questionnaires) distributed to students. The population in this study amounted to 3,594 students from the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara, with a sample of 98 students from Universitas Muhammadiyah Sumatera Utara, drawn with the Slovenian formula. The analysis method used is the path analysis model. The data processing method uses the Sempls application. According to Sempls, the results obtained in the study show that financial literacy has no significant effect on the financial behavior of students in business and business universities, and financial literacy has a significant effect on students' financial attitudes. Professor at North Sumatra School of Economics and Business, financial attitude has a significant impact on the financial behavior of students in economics and business schools, financial knowledge has no significant impact on financial behavior, financial attitude is a variable of mediation on students of the Muhammadiyah Sumatera Utara University of Economics and Commerce